Transient stent placement versus tubeless procedure after ureteroscopy retrograde surgery stone extraction (Fast Track Stent study 2): A randomized prospective evaluation. (6th July 2020) - Reicherz, Alina; Maas, Verena; Wenzel, Patricia; Dahlkamp, Lisa; Palisaar, Jüri; von Bodman, Christian; Noldus, Joachim; Bach, Peter
Abstract : Objectives: To determine whether in pre‐stented patients undergoing ureteroscopic stone removal (ureteroscopy retrograde surgery) a tubeless procedure provides a better outcome compared with short‐term (6 h) ureteral stenting using an external ureteral catheter. Methods: In this single academic center study (Fast Track Stent study 2), carried out between May 2016 and April 2018, 121 patients with renal or ureteral calculi were initially treated with double‐J insertion. Before secondary ureteroscopy retrograde surgery, patients were prospectively randomized into two groups: tubeless versus ureteral catheter insertion for 6 h after ureteroscopy retrograde surgery. Exclusion criteria were acute urinary tract infection, solitary kidney or stone diameter >25 mm. Study end‐points were stent‐related symptoms assessed by a validated questionnaire (ureteral stent symptom questionnaire), administered both before and 4 weeks after surgery. Numerical ureteral stent symptom questionnaire scores were compared using the Mann–Whitney‐ U ‐test. The level of significance was defined as P  < 0.05. Results: Ureteroscopy retrograde surgery procedures carried out by 13 surgeons resulted in >90% stone removal in all patients ( n  = 121), with a mean operation time of 19.9 versus 18.0 min for ureteral catheter versus tubeless, respectively ( P  = 0.37). Patient groups did not differ significantly in their ureteral stent symptom questionnaire scores (urinary index P  = 0.24; pain index P  = 0.35). Patients showed a significant preference for tubeless procedure over ureteral catheter reinsertion (Question GQ P  < 0.0001). The reintervention rate was 13.3% for the tubeless procedure ( n  = 8) and 1.6% for the ureteral catheter group ( n  = 1), respectively ( P  = 0.034). Conclusions: Short‐term ureteral catheter and no stent insertion after ureteroscopy retrograde surgery stone extraction in pre‐stented patients result in comparable quality of life. However, the reintervention rate is higher for tubeless procedures.